Community perceptions of the social and economic impacts of COVID-19 in Myanmar: Insights from round 3 of the National COVID-19 Community Survey (NCCS) – August and September 2020 - Oo, Than Zaw; Lambrecht, Isabel B.; Headey, Derek D.; Goudet, Sophie (International Food Policy Research Institute, 2020)
To better understand the economic and social impacts of the COVID-19 crisis on Myanmar’s diverse rural and urban communities, a multi-round large-scale community telephone survey is being conducted. The first round of the survey took place in June and July 2020, while the second round was done in August. This report focuses on key findings from the third round of survey done in August and September 2020. The survey obtained information from community respondents that had participated in the first or second rounds as well as from additional communities. In total, the third round obtained responses from 186 townships across Myanmar.